Mobile Security a Pocket Guide - Furnell, Steven (IT Governance Pub., 2009)
The book provides a concise reference to the key security issues affecting those that deploy and use mobile technologies to support their organisations. It aims to raise awareness of the threats to which mobile devices, users and data are exposed, as well as to provide advice on how to address the problems.